Fortalecimiento Institucional en La Caja Comunal Libertad y Desarrollo La Palma en la comunidad La Palma, parroquia Salinas, cantón Guaranda, provincia Bolívar, periodo 2024-2028 - Yanchaliquin Collay, Evelyn Mariela (2025)
The objective of this investigation is to strengthen the institution and determine how the Strategic Plan affects the growth of the Caja Comunal Libertad y Desarrollo “La Palma” in the province of Bolívar between the years 2024 and 2028. A detailed investigation was carried out that allowedxz us to verify the components of the Strategic Plan that have an impact on the progress of the organization. Because institutional strengthening, efficiency, motivation and job satisfaction impact the development of an organization, it is necessary to promote an adequate environment and a strategic plan focused on providing good service to members. Furthermore, it is crucial to examine how the strategic plan influences the activities carried out in the Fund. The findings of this research will help determine what elements are affecting the growth of the institution and develop methods to improve the work environment and, therefore, the services offered by the institution. The research consists of five chapters: the general formulation of the project, the theoretical framework, the methodology, the discussion of the results and the proposal, and then the conclusions and suggestions.